PENGEMBANGAN POP UP BOOK SEBAGAI MEDIA PEMBELAJARAN PADA MATERI DONGENG DI SD ISLAM AL-ALIFAH PALEMBANG - Dita Tri Wulandari; Liza Murniviyanti; Juaidah Agustina (Jurnal Binagogik, 2024)
This research's aim is producing a pop up book development product on fairy tail lesson that meets the criteria of validation and practice. This research uses the development research type (research and development). The development model on this research refers to ADDIE model which consists of 5 stages, such as analysis, design, development, implementation and evaluation. The subject of this research is the third year student of SD Islam Al Alifah Palembang. The data collection technique used was using a validation questionnaire sheet and a student response questionnaire. The expert validation data and student response questionnaire calculated using percentage formula. The results of the three validators produced a score with an average value of 93.3% with very valid criteria and suitable for use at the testing stage. The results of the questionnaire analysis of responses from the students of SD Islam Al-Alifah Palembang obtained an average score of 97.1% with very practical criteria. These data can be concluded that the development of pop-up books as a learning medium for fairy tale lesson has met the valid and practical criteria.